Electronic structure simulation of gallium arsenide clusters - Musa, Nor Muniroh (2009)
Semiconductor clusters have occupied the centre of scientific interest because of their unique electronic nature. Among the group III-V compound clusters, the gallium arsenide clusters have been the focus of this research due to their importance in constructing fast microelectric devices. The electronic structures of gallium arsenide clusters were studied. The simulations were carried out by using VASP (Vienna Ab-Initio Software Package) which utilizes the method of density functional theory (DFT) and plane wave basis set. Gallium arsenide clusters with surface passivated by hydrogen, GaxAsyHz were simulated to obtain the density of states (DOS) as well as bandstructure for each cluster. From the DOS graphs, discrete spectrum was observed instead of bulk-like continuous DOS which is the evolvement from bulk to nano-size. Bandstructure graphs also showed the discrete energy level in consistence with the discrete energy spectrum from DOS. It was found that the bandgaps for hydrogenated gallium arsenide clusters decreases with the increase in cluster size. Bare unhydrogenated gallium arsenide clusters, GaxAsy, with the number of atoms (x + y = 15) were also simulated. Optimization was performed to obtain the ground state structure. The bandgaps for the ground state gallium arsenide clusters do not show a decreasing trend with the increament of cluster size as that of hydrogenated gallium arsenide cluster. The electronic structures of optimized clusters are affected by the surface orientation of the clusters. Comparison of the bandgap values for GaxAsyHz and GaxAsy were also made.